I successfully evaluated the following integral using partial fraction expansion, but am unsure of a few steps.

$$ \int{\frac{x^2-2x-1}{(x-1)^2(x^2+1)}} = \int\left( \frac{A}{x-1} + \frac{B}{(x-1)^2} + \frac{Cx+D}{x^2+1} \right) \\\ \\ \\ x^2-2x-1 = A(x-1)(x^2+1) + B(x^2+1) + (Cx+D)(x-1)^2 \\\ \\ \\ x=1 \implies -2 = 2B \implies B = -1 \\\ \\ \begin{align} x=i \implies & -2-2i = (D+Ci)(i-1^2) = -2i(D+Ci) \\ \implies & -C+Di = 1+i \\ \implies &\ C=-1,\ \ D=1 \end{align} \\\ \\ \\ x^2-2x-1 = A(x-1)(x^2+1) - (x^2+1) - (x-1)^3 \\\ \\ \\ x=0 \implies -1 = -A \implies A = 1 \\\ \\ \\ \int{\frac{x^2-2x-1}{(x-1)^2(x^2+1)}} = \int\left(\frac{1}{x-1} - \frac{1}{(x-1)^2} + \frac{1-x}{x^2+1}\right) = \int \left( \frac{1}{x-1} - \frac{1}{(x-1)^2} - \frac{x}{x^2+1} + \frac{1}{x^2+1} \right) \\\ \\ \\ = \ln|x-1| + \frac{1}{x-1} - \frac{1}{2}\ln|x^2+1| + \arctan(x) + C\\\ \\ $$

My main points of confusion are:

  1. In general, how do you know which denominators to use in step 1?
  2. Is it okay to find the variables by plugging in values for $x$? Does this work in general? Is there anything I should be aware of, particularly where $i$ is involved?

2 Answers 2



  • Your way of using partial fractions is right, and it works in general.
  • Use this to find the partial fractions.
  • The integral of $\frac{1}{x}$ is equal to $\ln|x|+\text{C}$.
  • For $i$ notice that $i^2=-1$
  • When $a,b\in\mathbb{R}$:


  • $|a+bi|=\sqrt{\Re^2(a+bi)+\Im^2(a+bi)}=\sqrt{a^2+b^2}$

$$\int\frac{x^2-2x-1}{(x-1)^2(x^2+1)}\space\text{d}x=$$ $$\int\left[\frac{1-x}{x^2+1}+\frac{1}{x-1}-\frac{1}{(x-1)^2}\right]\space\text{d}x=$$ $$\int\left[\frac{1}{x^2+1}-\frac{x}{x^2+1}+\frac{1}{x-1}-\frac{1}{(x-1)^2}\right]\space\text{d}x=$$ $$\int\frac{1}{x^2+1}\space\text{d}x-\int\frac{x}{x^2+1}\space\text{d}x+\int\frac{1}{x-1}\space\text{d}x-\int\frac{1}{(x-1)^2}\space\text{d}x=$$ $$\int\frac{1}{x^2+1}\space\text{d}x-\int\frac{x}{x^2+1}\space\text{d}x+\int\frac{1}{x-1}\space\text{d}x-\int\frac{1}{(x-1)^2}\space\text{d}x=$$

For the intergand $\frac{x}{x^2+1}$, substitute $u=x^2+1$ and $\text{d}u=2x\space\text{d}x$:

$$\int\frac{1}{x^2+1}\space\text{d}x-\frac{1}{2}\int\frac{1}{u}\space\text{d}u+\int\frac{1}{x-1}\space\text{d}x-\int\frac{1}{(x-1)^2}\space\text{d}x=$$ $$\arctan(x)-\frac{1}{2}\int\frac{1}{u}\space\text{d}u+\int\frac{1}{x-1}\space\text{d}x-\int\frac{1}{(x-1)^2}\space\text{d}x=$$

For the intergand $\frac{1}{x-1}$, substitute $s=x-1$ and $\text{d}s=\text{d}x$:


For the intergand $\frac{1}{(x-1)^2}$, substitute $p=x-1$ and $\text{d}p=\text{d}x$:

$$\arctan(x)-\frac{1}{2}\int\frac{1}{u}\space\text{d}u+\int\frac{1}{s}\space\text{d}s-\int\frac{1}{p^2}\space\text{d}p=$$ $$\arctan(x)-\frac{\ln\left|u\right|}{2}+\ln\left|s\right|+\frac{1}{p}+\text{C}=$$ $$\arctan(x)-\frac{\ln\left|x^2+1\right|}{2}+\ln\left|x-1\right|+\frac{1}{x-1}+\text{C}$$

  • $\begingroup$ Thanks for the detailed answer. The Wikipedia page was helpful. Aside from the mistakes in the final step, am I reasoning correctly? I'm not sure what you're saying about $a+bi$. Is it not correct to reason $a+bi=x+yi \implies a = x+yi-bi = x$ (taking the real part) and then eliminating $a$ and $x$ to leave $xi=yi \implies x = y$? $\endgroup$
    – Zaz
    Jan 29, 2016 at 16:25

In general you factor the denominator (this can be hard), then

every linear factor $(x-a)^r$ gives you $r$ terms $\frac {A_1}{x-a}$, $\frac {A_2}{(x-a)^2}$, $\ldots$, $\frac {A_r}{(x-a)^r}$

every quadratic factor $(x^2+ bx+c)^s$ (it has complex roots, otherwise factor it to linear terms and apply the above) gives you $s$ terms $\frac {B_1 x+C_1}{x^2+bx+c}$,$\frac {B_2x+C_2}{(x^2+bx+c)^2}$, $\ldots$, $\frac {B_sx+C_s}{(x^2+bx+c)^s}$

Next step is to solve for $A_i$, $B_j$ and $C_j$. It's a linear system that has unique solution. In the end integrate all the remaining integrals


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .